2021
DOI: 10.1590/0100-3984.2020.0150
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis type 1: evaluation by chest computed tomography

Abstract: Objective: The aim of this study was to evaluate chest computed tomography (CT) findings in patients diagnosed with neurofibromatosis type 1 (NF1). Material and Methods: This was a retrospective study in which we reviewed the chest CT scans of 14 patients diagnosed with NF1 and neurofibromatosis-associated diffuse lung disease (NF-DLD). The sample comprised eight women and six men. The median age was 55 years (range, 11-75 years). The diagnosis of NF1 was made on the basis of the diagnostic criteria establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…In this particular case, the patient had a long history of NF-1 disease spanning over 30 years. Among patients with NF-1, there are variations in the clinical presentation, often accompanied by thoracic involvement such as intrathoracic neuro broma, intrathoracic meningoceles, spinal deformities, cysts, emphysema, subpleural bullae, interstitial pneumonia, and more [12,13]. Follow-up examinations have shown that lung involvement is more likely to occur in the advanced stages of NF-1, typically in patients in their thirties and forties.…”
Section: Discussionmentioning
confidence: 99%
“…In this particular case, the patient had a long history of NF-1 disease spanning over 30 years. Among patients with NF-1, there are variations in the clinical presentation, often accompanied by thoracic involvement such as intrathoracic neuro broma, intrathoracic meningoceles, spinal deformities, cysts, emphysema, subpleural bullae, interstitial pneumonia, and more [12,13]. Follow-up examinations have shown that lung involvement is more likely to occur in the advanced stages of NF-1, typically in patients in their thirties and forties.…”
Section: Discussionmentioning
confidence: 99%